A Rare Case of Uterine Torsion in a Goat - Dalal, Jasmer; Sangwan, Amit; Yadav, Rajendra; Dutt, Ravi (Animal Reproduction Update, 2022)
A doe at full term with the history of signs of abdominal discomfort and straining in for 6 hours was brought to clinics of Haryana Pashu Vigyan Kendra, Mahendergarh. Digital per-vaginum examination revealed post-cervical right side uterine torsion which was successful management by modified Schaffer’s method. Two kids of which one live and another dead were delivered with gentle traction. Animal recovered uneventfully after treatment with antibiotic and supportive therapy for five days.